Headache and sleep: Shared pathophysiological mechanisms. (September 2014) - Holland, Philip R
Objective: The objective of the current article is to review the shared pathophysiological mechanisms which may underlie the clinical association between headaches and sleep disorders. Background: The association between sleep and headache is well documented in terms of clinical phenotypes. Disrupted sleep-wake patterns appear to predispose individuals to headache attacks and increase the risk of chronification, while sleep is one of the longest established abortive strategies. In agreement, narcoleptic patients show an increased prevalence of migraine compared to the general population and specific familial sleep disorders have been identified to be comorbid with migraine with aura. Conclusion: The pathophysiology and pharmacology of headache and sleep disorders involves an array of neural networks which likely underlie their shared clinical association. While it is difficult to differentiate between cause and effect, or simply a spurious relationship the striking brainstem, hypothalamic and thalamic convergence would suggest a bidirectional influence.